Analysis and patterns of CD_ROM database use in Kenneth Dike library, university of Ibadan, Nigeria. (2004)
This study investigated the usage pattern of CD_ROM databases in Kenneth Dike library, university of Ibadan and how this facility meets the information needs of users. Data collected using: records of users between 1995-2001; 2 sets of questionnaire which satisfied and unsatisfied users and library staff, on how to improve services were entertained. Result showed that users were not very knowledgable on how to conduct a good/successful CD_ROM literature search; some CD_ROM databases are usually not very current, journal articles whose abstract were cited are not often available in the industry. Recommendations and suggestions whic included training of users and library personnel on how to conduct the CD_ROM literature searching, updating of CD_ROM databases, making available current journals in the library and effective library document delivery after a serach were made.